Mengelola Emosi Anak Lewat Aktivitas Positif dan Bermanfaat Pada Kegiatan PKL 1 di Panti Asuhan El-Shaddai Batam - Debora Manalu; Tuti Atika (Yayasan Literasi Sains Indonesia, 2022)
This Study aims to see the influence of positive activities that can benefit children in the el-shaddai orphanage through FieldWork Practice The method use in this research is descriptive qualitative with a case stufy approach.The results obtained through the implementation of positive activities in one of the children who experience emotional and personal problems who like to be angry at the orphanage can be concluded that the attitudes and behavior of children do not appear by themselves. one child. By paying attention to the condition of the living environment, peers and family can trigger the growth of children's attitudes and behavior. So the results obtained by applying rewards and inviting children to appear in public and inviting children to tell their problems are a positive activity that slowly changing the behavior of children who previously liked to be rude and harsh words too, children have changed and are acknowledged by friends who used to dislike their attitudes and behavior In this study, the author only carried out street vendors activities in one orphanage and focused on the problem of one child who was the author's client.In theory and practice, this paper will later be able to help readers in generating positive attitudes in children through the stages carried out by social workers.